If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
6*(x/2-(y/3)) = 6*(5/6) // - 6*(5/6)
6*(x/2-(y/3))-(6*(5/6)) = 0
6*(x/2-(y/3))-5 = 0
6*(1/2*x-1/3*y)-5 = 0
6*(1/2*x-1/3*y)-5 = 0
3*x-2*y-5 = 0
3*x-2*y-5 = 0
3*x-2*y-5 = 0 // + -2*y-5
3*x = -(-2*y-5) // : 3
x = (-(-2*y-5))/3
x = (5-(-2*y))/3
x = (5-(-2*y))/3
| 4y-10+y+60=5y+50-3y | | 4y-7=28 | | x/5-y/4=15/10 | | 5x-11y=44 | | 2ln(x+6)=4 | | 1/2x+2/3(-3+3x)=-19/2 | | (3x^2+9x+8)/(x+2) | | 12x+2y=18 | | (3-5i)(2+i)= | | 3x-(12)=3 | | (x^2+10x+20)/x+5 | | 1/2(1+1/3y)+2/3y=-19/2 | | y+3=-3/4x-(-3/4)*1 | | 2x-1/5+2x=19 | | 0.003*x^3+0.02*y^2=sin(0.01x^2) | | ((2x-1)/5)+2x=19 | | 4x+16/x^2+4x | | Yi=16-0.5xi | | 27x-24(-0.25+1.125x)=6 | | 7x+21y=63 | | 8y=9x-2 | | 32x-4(8x+6)=24 | | 15(.2)=4+5x | | 12x+2x=16 | | (2x+3)(x)=629 | | 15(-0.8+3y)-20y=-7 | | 5x=15y-4 | | -2(10-5g)-4g=9+16g | | 15y=4+5(-1/5) | | 284-5x=40x+19 | | Y/3+7=12 | | 2(y-3)=-2 |